2019
DOI: 10.1002/2050-7038.12006
|View full text |Cite
|
Sign up to set email alerts
|

Robust coordinated control for damping low frequency oscillations in high wind penetration power system

Abstract: The preeminence of wind power as a source of clean power generation is growing very fast. The increasing wind penetration, however, escalates the problem of low‐frequency oscillations (LFOs) in the modern grid. In this paper, LFOs damping improvement is presented for a high wind penetration power system by a robust coordinated control strategy of the power system stabilizer (PSS) and power oscillation damper (POD) of doubly fed induction generator (DFIG). This control strategy is achieved using an improved eig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…Electromechanical oscillations range from 0.1 to 3.0 Hz and arise from unbalanced torques at generators after generation and topology changes. Undamped oscillations reduce the limits of power interchange as well as the total amount of injected power by renewable sources 3,4 . Besides, LFO can also cause blackouts as reported in the literature 5 …”
Section: Introductionmentioning
confidence: 89%
“…Electromechanical oscillations range from 0.1 to 3.0 Hz and arise from unbalanced torques at generators after generation and topology changes. Undamped oscillations reduce the limits of power interchange as well as the total amount of injected power by renewable sources 3,4 . Besides, LFO can also cause blackouts as reported in the literature 5 …”
Section: Introductionmentioning
confidence: 89%
“…Also, application of the numerical methods involves large computation stress which consume excessive time and convergence rate is slow. 11,12 Another limitation with these approaches is, they are unable to reach global solution. 13,14 It is usually hard to find online optimal controller parameters with classical tuning controller methods due to the complexity and dynamical nature of the system.…”
Section: Introductionmentioning
confidence: 99%
“…However, it was reported that, for the design of PSS for interconnected multimachine systems operating on different conditions and configurations, these numerical methods involves representing the system mathematical models which is difficult for large system. Also, application of the numerical methods involves large computation stress which consume excessive time and convergence rate is slow 11,12 . Another limitation with these approaches is, they are unable to reach global solution 13,14 .…”
Section: Introductionmentioning
confidence: 99%
“…Increases both in the numbers of customers demanding for electrical energy as well as a reduction in fossil fuels have led to a shift toward renewable energy resources. Wind energy is the fastest growing renewable energy that may threaten the power system stability due to its large variability and penetration level . By increasing the penetration of wind resources, their impact on the dynamic stability of the power system has been increased.…”
Section: Introductionmentioning
confidence: 99%
“…Wind energy is the fastest growing renewable energy that may threaten the power system stability due to its large variability and penetration level. 1 By increasing the penetration of wind resources, their impact on the dynamic stability of the power system has been increased. The stabilization of low frequency oscillations (LFOs) is one of the most important issues in multi-area power systems with weak tie-lines.…”
Section: Introductionmentioning
confidence: 99%